Design of a randomized tobacco cessation trial among FDNY World Trade Center responders in a lung cancer screening program - David G. Goldfarb; Tyrone Moline; David J. Prezant; Matthew P. Bars; Rachel Zeig-Owens; Theresa Schwartz; Madeline F. Cannon; Brandon Vaeth; Julia H. Arnsten; Mayris P. Webber; Shadi Nahvi (Addiction Science & Clinical Practice)
Abstract Background Cigarette smoking remains the leading preventable cause of death, posing heightened risks for vulnerable populations. World Trade Center (WTC) disaster responders face an elevated burden of respiratory diseases, and despite access to an evidence-based tobacco cessation program, a subset continues to smoke cigarettes. Treatment engagement remains a critical barrier, as many people who smoke fail to enroll in or adhere to programs, particularly when participation requires decisions to actively opt-in to treatment. This randomized controlled trial integrates tobacco treatment into an existing low-dose computed tomography (LDCT) lung cancer screening program and compares the effectiveness of an Enhanced Care intervention with opt-out enrollment and biofeedback to Standard Care with opt-in enrollment and standard treatment. Methods The trial includes retired Fire Department of the City of New York (FDNY) responders aged 50 years or older who have a smoking history that satisfies either the National Comprehensive Cancer Network criteria of at least 20 pack-years or a simplified criterion of at least 20 years of smoking. Participants are randomized to either Enhanced Care, featuring opt-out enrollment in tobacco treatment with tailored counseling using biofeedback from chest LDCT and spirometry results, or Standard Care, requiring opt-in enrollment and standard tobacco treatment without biofeedback. Both arms receive a varenicline regimen with 4 weeks of pre-loading. Primary outcomes are treatment enrollment and biochemically verified 7-day abstinence. Factors associated with enrollment and abstinence, including retention, adherence, and quit motivation, will be evaluated. Discussion This trial addresses a key gap in tobacco cessation research by testing an innovative intervention for a high-risk occupational cohort participating in LDCT screening. The Enhanced Care model integrates opt-out enrollment, personalized biofeedback, and varenicline preloading to reduce smoking rates and health burdens in FDNY responders. Findings aim to inform scalable cessation strategies for both occupational and general populations, highlighting the need for novel approaches for hard-to-treat individuals who smoke. Trial registration This trial was registered at ClinicalTrials.gov under the identifier NCT05997225.